Efforts to Increase Interest in Reading in Grade 1 Elementary School Students with Media Pictures at Jali Gayamharjo State Elementary School, Prambanan, Sleman Yogyakarta Academic Year 2022/2023 - Eva Vera Santi (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research was conducted at SD Negeri Jali, Gayamharjo Village, Prambanan District, Sleman Regency, Yogyakarta Province. The time for conducting the research is in semester 2 of the 2022/2023 academic year. The research design used in this study is the Kurt Lewin model, namely the implementation of actions from one cycle to the next. Each cycle includes planning (planning), implementation (action), observation (observation) and reflection (reflection). Subjects in Classroom Action Research were grade 1 students at SD Negeri Jali, Prambanan, Sleman, Yogyakarta for the 2022/2023 academic year. The students totaled 10 students consisting of 4 male students and 6 female students. The data in this study are the results of observing the learning process, the results of students' reading skills, the results of students' enthusiasm for media images. In the form of data improving the learning outcomes of the subject matter theme 3 material obtained from the initial condition test, cycle I and cycle II